Tropical in Design Peunayong Traditional Market Building in Banda Aceh - syahrul aini; Syahrul Aini (Universitas Syiah Kuala, 2019)
The Peunayong market is the main market which visited by people in Banda Aceh and it’s surrounding area, in addition to trading activities, there is a religious activity. the existence of the new location of the vegetable and fruit market can eventually meet the needs of local communities especially in terms of food. In addition, the Government has also issued specific policies by providing a special market to selling for traders. The approach of design through the theme tropical architecture approach, i.e. studying the concept of space in the Building so that it can adjust to the climate. This design will also consider the behavior of the user market, and applies specific standards for users so that the future can make it easy, safe and convenient for the users of the market.